Work motivation and job satisfaction among local government health workers in Chitwan, Nepal: a cross-sectional study - Arjun Poudel; Sunita Poudel; Hari Prasad Kaphle; Sagar Parajuli (BMJ Public Health, 2025)
Introduction The health workforce is a crucial component of the WHO Health System Framework and is vital for sustainable, high-quality service delivery. Job satisfaction and motivation are key factors influencing the retention and performance of health workers. This study aimed to assess job satisfaction and its associated factors among health workers working under the local government in the Chitwan District, focusing on sociodemographics, job characteristics and work motivation.Methods A cross-sectional study was conducted among 219 health workers from 46 health facilities in the Chitwan district using a multistage sampling technique to include workers from various facility types and municipalities. Data were collected using a pretested, self-administered structured questionnaire and analysed with Statistical Product for Service Solutions V.22. Univariate, bivariate and logistic regression analyses were performed.Results The study found that 76.3% of participants were satisfied with their jobs. Opportunities for advancement (adjusted OR (AOR): 3.61, 95% CI: 1.35 to 9.66), nature of work (AOR: 3.54, 95% CI: 1.16 to 10.84) and supportive supervision (AOR: 3.58, 95% CI: 1.25 to 10.27) were significantly associated with higher job satisfaction.Conclusion Over three-quarters of health workers under local government were satisfied with their jobs. The study emphasises the significance of promoting supportive work environments, providing effective supervision and offering career development opportunities to enhance job satisfaction among health workers.